The 'Allah' controversy and other essays on Malaysian hypermodernity - Azly Rahman (Strategic Information and Research Development Centre, 2013)
Dr. Azly Rahman is one of Malaysia's intellectual hopes for the future. Although he currently resides in the United States his heart and mind is still very much in Malaysia, as this volume testifies to. In this collection, he is able to delve deeply into Malaysian consciousness and skilfully peel away each cultural layer to uncover the Malaysian psyche in a way never understood before, exposing our accepted national narratives for what they really are. A true patriot with hope and optimism about the future, Dr. Azly offers a framework for looking at some of the most pressing problems facing Malaysian society today. This volume will help every Malaysian think about what kind of Malaysia they all want for their children. - Murray Hunter - International Advisor to The 4th Media, Beijing, China International Advisor to Diplomatic Insight, Islamabad, Pakistan Associate Professor University Malaysia Perlis "From faraway in the USA Azly Rahman has made close observations on many issues besetting his beloved homeland. This book is very timely. It deals with current issues, some of which may be relevant to the thirteenth general elections. There are articles on the controversy over the 'Allah issue,' and there are also discussions on other topics that are hotly debated as we approach Malaysia's most intense elections. Azly is a very versatile writer as evident in this collection and is academically qualified to analyse the various subjects he has dwelt on. His writings are sometimes very challenging to read, but they are compensated by his depth of analysis. This volume is a must-read for those wishing to understand our society at a more complex level."